Mechanical engineers handbook. Volume 1 : Materials and engineering mechanics - Kutz, Myer (John Wiley & Sons Inc., 2015)
Full coverage of materials and mechanical design inengineering. Mechanical Engineers' Handbook, Fourth Edition provides a quick guide to specialized areas you may encounter in your work, giving you access to the basics of each and pointing you toward trusted resources for further reading, if needed. The accessible information inside offers discussions, examples, and analyses of the topics covered. This first volume covers materials and mechanical design, giving you accessible and in-depth access to the most common topics you'll encounter in the discipline: carbon and alloy steels, stainless steels, aluminum alloys, copper and copper alloys, titanium alloys for design, nickel and its alloys, magnesium and its alloys, superalloys for design, composite materials, smart materials, electronic materials, viscosity measurement, and much more"--Provided by publisher.